2013
DOI: 10.1007/s12033-013-9670-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protective Effect of Antisense Oligonucleotide Developed Against the Common 3′ NCR of Influenza A Virus Genome

Abstract: The influenza A virus (IAV) has eight segmented single-stranded RNA genome containing a common and evolutionarily conserved non-coding region (NCRs) at 5' and 3' ends that are important for the virus replication. In this study, we designed an antisense oligonucleotide against the 3' NCR of vital segments of the IAV genome to inhibit its replication. The results demonstrated that the co-transfection of Madine Darby Canine Kidney (MDCK) cells with the antisense oligonucleotide and the plasmids encoding the viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…the noncoding region located on the 3’-end of (+)cRNA after the stop codon (1544–1564), the nearby coding region close to the stop codon (1498–1516), the region including the AUG codon (34–54), and the 5’-noncoding region (2–22), where the nucleotide numbering is given for (+)cRNA. The short 5’- and 3’-terminal nontranslated regions (NTRs) are of considerable interest because all eight RNA segments of various IAV subtypes are known to contain conserved sequences of 13 or 12 nucleotides at their 5’ and 3’ ends ( 5’ AGUAGAAACAAGG 3’ and 5’ CCUGCUUUUGCU 3’ , respectively) [2021]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the noncoding region located on the 3’-end of (+)cRNA after the stop codon (1544–1564), the nearby coding region close to the stop codon (1498–1516), the region including the AUG codon (34–54), and the 5’-noncoding region (2–22), where the nucleotide numbering is given for (+)cRNA. The short 5’- and 3’-terminal nontranslated regions (NTRs) are of considerable interest because all eight RNA segments of various IAV subtypes are known to contain conserved sequences of 13 or 12 nucleotides at their 5’ and 3’ ends ( 5’ AGUAGAAACAAGG 3’ and 5’ CCUGCUUUUGCU 3’ , respectively) [2021]. …”
Section: Resultsmentioning
confidence: 99%
“…The coding region close to the stop codon was often used as the target for the action of siRNA [9,12,1516]. The other regions of the NP gene were also studied as targets [8,1112 21]. It can be concluded from these literature data that the most susceptible regions for the action of NA-based drugs are the first two regions mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implied that a single antisense oligonucleotide could provide protection against more than one strain of influenza A virus. 90 Another in vivo study carried out by Tompkins et al revealed that influenza-specific siRNA treatments directed against the NP and PA genes were broadly effective and protected animals against lethal challenge with highly pathogenic avian influenza A viruses of the H5 and H7 subtypes. 91 Ge and co-workers also reported that siRNAs targeting the NP and PA gene segments (NP-1496 and PA-2087, respectively) provided a broadly effective inhibition of H1N1 influenza virus.…”
Section: Broad Anti-influenza Spectrum and Long-term Inhibitory Effectmentioning
confidence: 99%
“…The recent dissection of the RNA processing and control has opened up the frontiers to innovative concept of antiviral therapy based on nucleic acid RNA interference (DeVincenzo, 2012;Spurgers et al, 2008) cleotides as potential antivirals have already been used by different research groups for many pathogenic respiratory viruses (Spurgers et al, 2008;DeVincenzo, 2012), including the influenza virus (Wong et al, 2010). In this context, antivirals based on antisense oligonucleotides, small RNA interfering molecules and microRNAs (miRNA) targeting different sequences of influenza virus genome have been reported (Li et al, 2011;Kumar et al, 2013;Ge et al, 2006;Kwok et al, 2009;Abe et al, 2001;Duan et al, 2008). Influenza virus genomic segments encoding for the viral polymerase subunits (PA, PB1 and PB2), have been described to play a pivotal role in the hierarchy of segment interactions,during the packaging of viral genome into the newly assembled particles (Palese and Shaw, 2007;Hutchinson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%